Analyzing the Potential of the Doctor’s House (Dokterswoning) in Metro City as a Local-Based History Learning Resource in Lampung - Bahtiar Afwan; Muhammad Rijal Fadli; Agung Dian Putra (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to analyze the potential of the Doctor’s House (dokterswoning) in Metro City as a source of history learning in Lampung. The research employed a qualitative approach with a case study design conducted at the Rumah Informasi Sejarah (RIS) of Metro City. The research subjects included history teachers, students, and RIS managers selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, while data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the dokterswoning possesses significant historical and architectural value as a learning resource, as it represents Dutch colonial policies and serves as an authentic physical evidence of the past. Its utilization in history learning creates contextual and meaningful learning experiences, enhances students’ historical thinking skills, and fosters historical awareness as well as appreciation toward cultural heritage. However, its implementation remains suboptimal due to limited teacher competence, the dominance of conventional teaching methods, and the lack of integration into instructional planning. Therefore, innovation in developing local history-based learning models and improving teachers’ competencies are necessary to optimize the use of dokterswoning as a contextual and meaningful history learning resource.